Firm Size, Ownership and Performance in the Malaysian Palm Oil Industry - Bala Ramasamy; Darry Ong; Matthew C. H. Yeung (Asian Academy of Management Journal of Accounting and Finance, 2005)
The objective of this study is to analyse the effects of market structure components and other performance measures to better understand the dynamics and determinants of performance within the Malaysian palm oil sector. In particular, we consider the effects of firm size and firm ownership on the level of profitability in this sector. Our findings suggest that size is negatively related to performance while privately owned plantation companies are more profitably managed. These results support the recent move by the Malaysian government to postpone the listing of the Federal Land Development Authority (FELDA), a government agency responsible for managing government land schemes and commercial development of plantations. It also lends support to the ongoing strategy of improving the performance of Government Linked Corporations (GLC) in Malaysia.